Attributes of Project-Friendly Enterprises. - Anantatmula, Vittal S. (Portfolio and project management collection., 2016)
The objective of any organization is to create value for its stockholders. Given that sophistication in project management will lead to efficiency in operations, which in turn leads to better profits, enlightened enterprises are sensitive to project management sophistication and the definitive way of measuring it and improving it. Although in many organizations, projects are initiated in isolation of each other, and based on ad hoc urgencies, sophisticated enterprises have a formalized, logical, and consistent, structure for organizing, and managing, their projects. Project management sophistication is the state of enterprise practices in which success of projects is predictable and that the definitive measure of project management success continually improves with time. Conducting a full assessment of the organizational project management sophistication is relatively time consuming and costly. Thus, many organizations have a need and desire for instruments that would provide a rough estimate of the project management maturity of the organization without a major expenditure of funds. This book includes instruments that should help in that regard.